Physicochemical Analysis of Some Soft Drinks Available in Nepal - Ghimire, Sadiksha; Niraula, Muna; Tandukar, Pooja; Thapa, Prakash; Pathak, Ishwor (Amrit Journal, 2024)
This work aimed to check the physicochemical parameters of some soft drinks available in Nepal. Coca-Cola, Pepsi, Fanta, Sprite, Rio juice, and Red Bull were taken from the nearby stores for the experiments. The determination of ascorbic acid, phosphoric acid, acid value, corrosiveness, amount of caffeine, dissolved oxygen, biological oxygen demand, and chemical oxygen demand was carried out by using several materials and chemical reagents as per the established protocols. All the samples were taken from their bottle or can exactly at the time of experiments. The obtained results from this work were compared to the standard values and the possible health effects of overconsumption were discussed. From the calculation, Coca-Cola was found to be highly acidic (pH 2.3), Pepsi was found to contain the highest amount of ascorbic acid (0.126 g) and dissolved oxygen (22.4 g/L), and Red Bull was found to contain the highest amount of caffeine (2.6345 g/L). Red Bull was found to have the highest percentage of weight loss on mild steel (1.12 %).